Public Speaking Anxiety in a Real Classroom: Towards Developing a Reflection System - Lee, Heera; Kleinsmith, Andrea (ACM, 2019)
Public speaking is recognized as an important skill for success in learning and education. However, the mere thought of public speaking elicits anxiety in many people. This anxiety may manifest in a student's nonverbal behaviors and physiological responses which can negatively affect both performance and evaluation. While public speaking training systems have employed a variety of speaker cues to automatically evaluate and score public speaking performance, many are built on data collected in a lab setting. However, it is difficult to achieve the same level of anxiety in these environments. We posit that students would benefit from a system that provides the ability to reflect on and practice public speaking presentation skills. This preliminary study explores public speaking anxiety from physiological responses and nonverbal behaviors of English language learners in-situ as a first step toward the design and development of a public speaking practice and reflection system.
CHI EA '19: Extended Abstracts of the 2019 CHI Conference on Human Factors in Computing Systems, May 2019
Keywords: Public speaking anxiety; Electrodermal activity; Nonverbal behaviors; Affective computing; Reflection